Pengaruh Senam Hamil Terhadap Penurunan Nyeri Punggung Bawah pada Ibu Hamil TM II di Puskesmas Sidomulyo Banyuasin Tahun 2023 - Ina Fitriana; Ester Simanullang; Sri Muliana Putri Bakara (STIKes Ibnu Sina Ajibarang, 2024)
Maternal Mortality Rate (MMR) is a component of the development index and quality of life index which is calculated by considering and taking into account women's health status (MMR). The aim of this study was to determine the effect of pregnancy exercise on reducing lower back pain in pregnant women III at the Sidomulyo Banyuasin Community Health Center. The research population was pregnant women in the third trimester at the Sidomulyo Banyuasin Community Health Center with a total of 16 pregnant women. Univariate and bivariate data analysis. The results of research show that pregnancy exercise has an effect on reducing lower back pain in pregnant women. This shows that 0.018 is smaller than 0.05. Through this research, pregnant women understand the benefits of pregnancy exercise during pregnancy, especially during the third trimester of pregnancy, which has a very good impact so that mothers feel comfortable and reduce complaints during pregnancy, such as lower back pain, especially.